Solar energy storage and release application of water-phase change material- (SnO2-TaC) and (SnO2–SiC) nanoparticles system - Farhan Lafta Rashid; Aseel Hadi; Ammar Ali Abid; Ahmed Hashim (International Journal of Advances in Applied Sciences, 2019)
The thermal energy  storage and release application of water- phase change material- (SnO2-TaC) and (SnO2–SiC) nanoparticles system has been investigated for cooling and heating applications. The water - polyethylene glycolwith (SnO2-TaC) and (SnO2–SiC) nanoparticles have been used. The results showed that the melting and solidification times for storage and release of thermal energy of water - polyethylene glycoldecrease with increase in(SnO2-TaC) and (SnO2–SiC) nanoparticles concentrations. The melting and solidification times decrease with increasing of TaC nanoparticles concentrations to water-polyethylene glycol/SnO2nanofluidand SiC nanoparticles concentrations to water-polyethylene glycol/SnO2nanofluid.